Cytogenetic analysis of the Pampas deer, Ozotoceros bezoarticus (mammalia, cervidae) - Barbanti Duarte, J. M. [UNESP]; Luz Giannoni, M. [UNESP] (My University, 1995)
The chromosome constitution of five males and three females of the Pampas deer (Ozotoceros bezoarticus) coming mainly from the region of Corumba-MS, was studied. The diploid number of the species was reconfirmed as 68 chromosomes with Fundamental Number (FN) = 74. The X chromosome was the largest and the Y the smallest in the genome. Constitutive heterochromatin demonstrated by C banding was present in the centromeric region of all chromosomes, except in pair number two, which had none, and in chromosome X which had a stained region in the telomere on the long arm. Chromosomes pairs 3 and 4 bore Ag-NORs. The banding patterns differed from those of previous reports for this species. This may be due to subspecific differences.